Utilizing TikTok as A Promotional Platform for Small and Medium Enterprises: A Strategic Approach - Islami, Wahyu Nurul; Putra, Yudiarto Perdana; Triwidyati, Endang (Target : Jurnal Manajemen Bisnis, 2024)
Advances in digital technology, such as the emergence of TikTok, have changed how we live, work, and communicate. TikTok is used as an entertainment medium and as a platform to promote businesses because it can reach the target market easily through creative content. This research aims to determine the strategy for using TikTok social media as a promotional medium for Small and Medium Enterprises (SMEs), such as Sultan Mango Malang. The method used is a descriptive qualitative approachData collection techniques were carried out through documentation, observation, and interviews, then analyzed using the data triangulation method. The results of this study show that the strategies successfully implemented by the SMEs include actively following popular trends, interacting directly with the audience, utilizing the live streaming feature, consistently uploading content, working with influencers, and holding discount promos and prizes. It also shows that user participation and interaction are the main keys to assessing the success of TikTok's promotional strategy. Sultan Mango Malang can increase product awareness and improve the quality of services provided as they actively respond to every form of user interaction quickly. Therefore, the findings of this research significantly contribute by offering comprehensive and actionable insights for local enterprises and SMEs aiming to leverage TikTok effectively to enhance sales figures and foster long-term customer loyalty.